歯科医療における機能分化と連携−病院歯科口腔外科 未来への切符 - 薬師寺, 登; 萩野, 浩子; 和田, 康志; 竹信, 俊彦; 堀江, 彰久; 山下, 徹郎; 藤盛, 真樹 (日本口腔外科学会雑誌, 2016)
Advances in medical and demographic change due to aging, dentistry and oral surgery care has changed significantly. In point of the dental care in Japan, hospital dentistry and oral surgery improves the quality of treatment and the patient’s safety and secure. It has become necessary and essential. Hospital dentistry and oral surgery with a seamless cooperation with other departments and different jobs in hospital is believed to be a significant contribution to the future of dentistry.　As shown in this paper, hospital dentistry and oral surgery according to the needs has various functions. Its significance is noted and necessity. It enhances the knowledge, the technology and the surgical techniques. Advanced oral surgery expertise and the cooperation of local and in-hospital seemed to be a mission of hospital dentistry and oral surgery. It increases the need for hospital dentistry and oral surgery in the future.　At the same time this was believed to contribute significantly to improve the quality of local dental care and hospital dental oral surgery.